Future Specialists in Physical Culture and Sport Communicative Competence Development by Training Methods - Beseda, Nataliia; Martynenko, Anatolii; Moroz, Yurii (International Journal of Engineering and Technology, 2018)
Scientific approaches to the of â€œcommunicative competenceâ€ definition are generalized and analyzed by the authors. Classification of training methods is carried out. The peculiarities of communicative competence development in the specialty 017 â€œPhysical Culture and Sportâ€ on the basis of training methods application during studying of the â€œPsychologyâ€ subject are revealed. The importance of communicative competence in the structure of future specialists in physical culture and sports professional activity is substantiated. It has been proved that in the process of professional training the students’ ability to communicate effectively is of special importance. The article examines the essence of pedagogical communication, its functions and styles. The influence of communicative competence on a specialistâ€™ professional skills formation has been characterized. Barriers to communication and approaches to their elimination are defined and described. Exercises for the development of studentsâ€™ constructive communication skills on the basis of future professional activity modeling are offered. The results obtained in the course of pedagogical experiment confirm the effectiveness of the training methods usage in the process of future specialists in physical culture and sports communicative competence development. Â Â Â